PRODUÇÃO, CIRCULAÇÃO E RECEPÇÃO DO JORNALISMO CONTEMPORÂNEO: BREVE PANORAMA - Sampaio, Claudiane Oliveira Carvalho (Animus. Revista Interamericana de Comunicação Midiática, 2021)
This text proposes to outline a brief overview of the conditions of production, circulation and consumption of journalism in a social context of deep media coverage, marked by ubiquity and interconnection. Critical-analytical, the article includes a literature review that combines studies of journalism with sociosemiotics, with the premise that media coverage promotes the autonomy of journalistic discourse in time and space and also fosters the access revolution. In the course of the information production cycle, circulation emerges with an instance of repositioning reception, also reconfiguring the role of production and catalyzing new communicative contracts.